2019
DOI: 10.1109/access.2019.2891544
|View full text |Cite
|
Sign up to set email alerts
|

Cold Start Recommendation Based on Attribute-Fused Singular Value Decomposition

Abstract: Collaborative filtering plays an important role in promoting the service recommendation ecosystem, and the matrix decomposition technology has been proven to be one of the most effective recommendation methods. However, the traditional collaborative filtering algorithm has great shortcomings in the recommendation of cold start items, especially the emergence of new items will be largely ignored. This not only has a very bad impact on the development of the item, but also greatly reduces the diversity of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…. The rating predictions were made by combining Equations (9) and (12) and utilizing the following objective function for the minimization task:…”
Section: Incorporating Tag Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…. The rating predictions were made by combining Equations (9) and (12) and utilizing the following objective function for the minimization task:…”
Section: Incorporating Tag Informationmentioning
confidence: 99%
“…Memory-and model-based techniques are commonly used to elucidate CF recommendations [3,[11][12][13][14][15]. Past studies have demonstrated the benefits of memory-based CF, wherein rating predictions are computed from the preferences of similar users via a rating matrix [12,[16][17][18][19]. Conversely, the model-based CF technique leverages a user-item rating matrix to initially build a predictive model using deep learning methods and then source the rating predictions from it [3,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, this form of representation is prone to produce considerable invalid information, especially when the dimensions are very high [27]. Although the truncated SVD (singular value decomposition) [8], [11] technique for low-rank factorization can extract the metadata from high-dimensional data, the correlation between various types of data has not been fully considered. Moreover, this category of principal component extraction technique cannot flexibly combine extracted metadata to improve performance.…”
Section: A Scalable Context Encoder (Sce)mentioning
confidence: 99%
“…The key to solving this problem is how to make full use of user profiles to predict their behavior. A user's profile can be the user's own attribute [6]- [8] or other information besides the behavior. We collectively refer to this available user information as user profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation